PASSENGER CAR TRANSPORTATION MANAGEMENT REQUIREMENTS IN MANDONGA TRAYEK MALL - TERMINAL PUWATU AND MANDOGA MALL - LABIBIA IN KENDARI CITY - Muhammad Irsan Basalamah (Jurnal Manajemen Rekayasa (Journal of Engineering Management), 2021)
Kendari City is the Capital City of Southeast Sulawesi Province which continues to experience development from year to year. The centralization of the activities of the Provincial Government, the large number of educational institutions, adequate health facilities, modern shopping centers, airports, etc. are reasons for the high dependency of the regions in the Southeast Sulawesi Province administrative area on Kendari City, so a reason or attraction for people from other regions to travel and settle in Kendari City. To serve the community movement, the role of transportation is very important especially land transportation, so there are many public transportation in Kendari City with a variety of routes, one of which is public transportation at the Mandonga Mall - Termal Puwaatu and Mandonga - Labibia Mall, which serves the movement of the community from Mandonga Mall. , wet market and Kendari City Mandonga roundabout to Puwatu and Labibia terminals or vice versa.               Puwaatu terminal is a liaison for car transportation to the districts of Konawe, Konawe Utara, Kolaka and Kolaka Utara or vice versa. So that the role of public transportation Puwaatu terminal route to the Mandonga Mall Kendari is urgently needed to serve the movement of the community and the Mandonga Labibia Mall route to Konawe Regency, because the movement of the people from these districts is generally a movement of people who travel from several Regencies to Kendari City or vice versa . So we need a policy from the government so that the service system can run smoothlyFrom the results of research conducted on existing problems, it can be concluded that the characteristics of public transport passenger trips in the city of Kendari public transportation with a capacity of 11 people show the number of passengers per trip (round trip) on all routes of Mandonga - Puwaatu and Mandonga Mall - Labibia in the city of Kendari ranges from 13 passengers to 20 passengers, or an average of 16 passengers per trip. For Mandonga - puwaatu mall routes, the number of passengers per route is quite large, namely 13 passengers per route, this is due to the length of the routes on this route so that passengers get up and down quite large, and the limited number of fleets on the route and the availability of the number of fleets to the needs of transport passengers general microlet in Mandonga Mall Route - Puwatu Terminal and Mandoga Mall - Labibia in Kendari City Based on Load Factor in the current field, the number of microlet public transport fleets that should be available according to the number of passengers in Mandonga Mall - Puwaatu Terminal in Kendari City is 5 units existing vehicles and the Madonga Mall - Labibia route, adding 1 vehicle to the current vehicle. Keywords: Route, Passenger Cars, availability